2019
DOI: 10.1063/1.5055731
|View full text |Cite
|
Sign up to set email alerts
|

Strain-dependence of χ(2) in thin film barium strontium titanate

Abstract: Optical second-harmonic generation (SHG) in reflection characterized variations in the second-order nonlinear optical susceptibility χ(2) of Ba1−xSrxTiO3 (BSTO) alloy films grown epitaxially on SrTiO3(001) (STO) as Sr molar ratio x changed from 0 to 1 and thickness from 10 to 50 nm. X-ray diffraction showed that BSTO films with x ≳ 0.1 were highly crystalline and compressively strained with out-of-plane (in-plane) lattice constant 4.09 > c > 3.97 (3.903 < a < 3.907 Å, pinned to subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Although non‐ferroelectric BTO films or powders stabilize in cubic symmetry, particularly for small grain size, the film under current study retains non‐vanishing EO response, which would not be present in crystal structures with inversion symmetry. Frey and Payne demonstrated that ultra‐fine‐grained, sol‐gel‐derived BTO powder can exhibit room temperature orthorhombic structure and maintain non‐zero second harmonic generation, which is also a second‐order nonlinear optical effect . The small and disperse grain sizes observed in the film, in combination with the relatively high defect density (Figure ), which also provides sources for depolarizing effects, are likely the primary contributors to the absence of finite macroscopic polarization and overall diminished EO response.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although non‐ferroelectric BTO films or powders stabilize in cubic symmetry, particularly for small grain size, the film under current study retains non‐vanishing EO response, which would not be present in crystal structures with inversion symmetry. Frey and Payne demonstrated that ultra‐fine‐grained, sol‐gel‐derived BTO powder can exhibit room temperature orthorhombic structure and maintain non‐zero second harmonic generation, which is also a second‐order nonlinear optical effect . The small and disperse grain sizes observed in the film, in combination with the relatively high defect density (Figure ), which also provides sources for depolarizing effects, are likely the primary contributors to the absence of finite macroscopic polarization and overall diminished EO response.…”
Section: Resultsmentioning
confidence: 99%
“…Frey and Payne demonstrated that ultra-fine-grained, sol-gel-derived BTO powder can exhibit room temperature orthorhombic structure and maintain non-zero second harmonic generation, 22 which is also a second-order nonlinear optical effect. 44 The small and disperse grain sizes observed in the film, in combination with the relatively high defect density (Figure 4), which also provides sources for depolarizing effects, are likely the primary contributors to the absence of finite macroscopic polarization and overall diminished EO response. Indeed, high Pockels coefficients are correlated with larger grain sizes.…”
Section: Resultsmentioning
confidence: 99%
“…Electric field and strain are important factors in tuning ferroelectrics [54,55,122]. They always couple with each other, and deduce to many fantastic properties.…”
Section: Domain Structure Modulation and Multifield Responsementioning
confidence: 99%
“…A typical ferroelectric material usually has two polarization states, which are stable and can be converted reversely to each other by applying electric fields [51]. Moreover, ferroelectric polarization can be tuned by temperature and strain [52][53][54][55]. It is reported that ferroelectrics possess various interactions between mechanical, thermal, and electrical characteristics [56].…”
Section: Introductionmentioning
confidence: 99%